Hemorrhoids: which is the best therapeutic option? - Vagholkar, Ketan; Chawathey, Shreyas; Shekhar, Shantanu; Vagholkar, Suvarna (International Surgery Journal, 2018)
Hemorrhoids are one of the commonest of rectal diseases seen all across the globe. Constipation and bleeding are the main symptoms associated with this condition. The condition maybe associated with an underlying carcinoma as well. Understanding the pathophysiology will enable the surgeon to determine the best therapeutic option for this condition. A brief review of clinical evaluation and treatment options is presented in this paper.